Dynamic analysis of reinforced concrete structures - P. Tamayo, Jorge L. (2012)
The objective of this work is to provide a reliable numerical model using the finite element method (FEM) for the dynamic analysis of reinforced concrete (RC) structures. For this purpose, a computer program based on a strain-rate sensitive elasto-plastic theory is developed using 3D brick finite elements. The implicit Newmark scheme with predictor and corrector phases is used for time integration of the nonlinear system of equations. In addition, the steel reinforcement is considered to be smeared and perfectly adhered to concrete and represented by membrane finite elements. Two benchmark examples are analyzed with the present numerical model and results are compared with those obtained by other authors. The present numerical model is able to reproduce the path failure, collapse loads and failure mechanism within an acceptable level of accuracy.